The degree of the contribution of the Jordanian Teachers Union in achieving job security for its employees from the point of view teachers in Ajloun Governorate - Al-Momani, Taghreed Radwan (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the degree of the Jordanian Teachers ’Union’s contributions to achieving job security for its members from the teachers’ point of view in Ajloun Governorate and to know the effect of the variables (gender, educational stage, school type) on teachers ’assessments of the degree to which their managers practice those standards. To achieve the study’s objectives, the researcher used the descriptive survey approach The questionnaire was also used. It was distributed on a sample of (380) male and female teachers, who were chosen by the simple random method. The results of the study showed that the degree of the Jordanian Teachers ’Union’s contributions to achieving job security for its members from the teachers’ point of view in Ajloun Governorate was moderate, and that there was no effect of the variables (gender, educational stage, school type) on teachers ’assessments, and the study recommended the necessity for the teachers’ union to participate with the Ministry of Education. And education in achieving the goals and aspirations of the union in serving the educational system in the whole Kingdom, spreading the culture of union work and increasing interest in teachers affiliated with it in all public and private schools in all governorates.